USE OF HUMIC SUBSTANCES AND MICROORGANISMS IN JAPANESE CUCUMBER PRODUCTION - Grunewald Júnior, Eumar (2021)
Cucumber (Cucumis sativus) is a crop of great economic and social importance within the vegetable agribusiness in Brazil, being consumed in all Brazilian regions. The use of microorganisms or substances that can positively influence the improvement of one or more plant characteristics is already a necessity in agriculture. Therefore, the objective was to evaluate the vegetative development and production of the Japanese cucumber crop using products based on humic substances and nutrient-providing microorganisms. The use of 100, 50 and 0% of the recommended mineral fertilizer for the culture was tested, as well as a set of three products composed of microorganisms and a product based on Humic Substances, with two levels of fertilizer each (50% of the recommended mineral fertilizer and without mineral fertilizer). The use of products associated with 50% of the recommended mineral fertilization provided the achievement of production levels equal to or greater than those found when using 100% of the fertilization. For the variables of vegetative development, equal results were found for the treatments with the use of products associated with 50% of the fertilization and the treatment with 100% of the chemical fertilization recommended for the culture.